Prevalence of hypertension and associated risk factors among the chinese elderly in Perkampungan Berapit and Prkampungan Sungai Lembu Seberang Prai Tengah, 1994 - Teo, Gim Sian; Md. Idris Mohd Nor (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross-sectional study was carried out to determine the prevalence of hypertension in the elderly and to study the relationship between hypertension in the elderly and various sociodemographic, behavioural and nutritional factors. This study involved an the Chinese elderly persons aged 55 and above in 2 randomly selected Chinese villages in Seberang Prai Tengah, Pulau Pinang. This study included house to house interview, anthropometric assessment and blood pressure measurement. The prevalence of hypertension was 48.1% and out of this, 65 (55.6%) were aware of having hypertension and were on treatment. There was a significant rise in the prevalence with age. There was no significant difference in the prevalence in both sexes. Hypertension was found to be inversely related to per capita income. Hypertension was significantly more common in smokers than non-smokers and in those with positive family history. Hypertension was found to be inversely related to physical activity (p<0.05). There was no significant difference between the dietary intake of sodium, potassium, calcium, vitamin C and fat in the hypertensives compared to the normotensives. Alcohol intake in the elderly was low and not related tohypertension. From the multivariate analysis, age, smoking, physical activities and family history were the main independent factors that determined the prevalence of hypertension and systolic blood pressure. Physical activity and BMI were the main predictors of diastolic blood pressure.